PERENCANAAN WISATA MANGROVE KAMPUNG KELEMBAK KOTA BATAM - I Nyoman Budiartha; Rindi Purnawan (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
The ecosystem of Mangrove Forest in Kelembak Village, Batam city is in decent conditions, potentially can be developed as community-based to provide economic benefits for the local community and stimulate the reawakening of local tourism activity. This research aims to find out the factors affecting mangrove conservation activities and attain the precise mangrove forest planning development for educational tourism destination. This study was conducted in October 2021 in Kelembak Village, Nongsa subdistrict using qualitative approach with descriptive methods. The technique of determining the informants was purposive sampling with observation and in-depth interviews. The data obtained is analyzed using SWOT analysis (Strengths, Weakness, Opportunity and Threat). The results of the analysis the factors that influence the development of mangrove conservation activities in Kelembak Village are internal factors including the condition of mangrove forests, scope of the area, involvement of government and private institutions, community involvement, community cohesiveness, availability of facilities, and supervision. External factors include the potential for making mangrove processed products, the potential of ecotourism, and the potential as an object of research with participation of academicians. The preferred alternative strategic priority is to intensify collaboration with government and private institutions to strengthen funding sources for each activity, expanding mangrove explored area, improve operational support facilities and involving the community in every activity.